Farmers' perceived costs of wetlands: effects of wetland size, hydration, and dispersion - Gelso, Brett R.; Fox, John A.; Peterson, Jeffrey M. (My University, 2012)
We survey landowners to investigate the costs associated with the presence of permanent or seasonal wetland areas in cropland. We find, as predicted by our conceptual model, that dispersion of wetland areas imposes substantial inconvenience costs for producers but that costs respond nonlinearly and irregularly to changes in the frequency of hydration. Producer attitudes toward conservation and environmental regulation have a significant impact on perceived costs, as do some demographic attributes. The analysis suggests that incentives to aggregate dispersed wetlands into larger contiguous areas could benefit landowners while at the same time provide a net increase in wetland area.
Keywords: Perceived costs; Wetlands